(untitled) (Global Journals of Research in Engineering, 2013)
The aim of this paper is to investigate the handoff / handover concepts in wireless communication. Mobility is the distinct feature of wireless mobile cellular system. As a mobile subscriber move between different radio networks, a handover process is needed to change its point of attachment. The continuation of an active call is one of the most important quality measurements in cellular systems. Handoff process enables a cellular system to provide such a facility by transferring an active call from one cell to another. Usually, continuous service is achieved by supporting handoff which is the transfer of an ongoing call from the current cell to the next adjacent cell as the mobile moves through the coverage area. The paper represents the current approaches of handoff initialization, detection strategies and their relative benefits and disadvantages.